posted by on .

1. Simplify 49^3/2.

2. Simplify 5^ãx^25y^125.

3. When the polynomial 5x - 2x + 8x^2 - 7 is written in standard form, what is the leading coefficient?

4. Classify the polynomial 5x^2 + 9x + 1 according to tis degree and number of terms.

5. Genie has 100 feet of fence with which to make a rectangular cage for her rabbit. If she uses the wall of her house as one side, the area of the cage in square feet is given by the polynomial -2x^2 + 100w, where w is the width of the cage in feet. What is the area of the cage if the width is 15 feet?

6. Add (5x^2 - 2x + 9) + (2x^2 - 4).

My answer: 7x^4 - 2x + 5?

7. Subtract (10a^2 - 6a) - (7a^2 - 8a).

8. Multiply (-5rs^4)(3r^5s^2).

9. (3x - 4)^2

My answer: 6x^2 - 24x + 8?

10. (2x + 4)(2x - 4)

• Algebra 1 Answer Check - ,

1. correct if you meant 49^(3/2)
The way you typed it --- 117649/2

3. the leading term in standard notation would be 8x^2

4. correct

5. the x is undefined in your problem

6. 7x^2 - 2x + 5, the exponent is not affected when adding like terms

7. 3a^ + 2a

8. correct

9. 6x^2 - 24x + 16 , 4 x 4 = 16 not 8

10. 4x^2 - 16

looks like somebody has some serious studying to do.

• Algebra 1 Answer Check - ,

1.

If 49^3/2 mean 49 ( 3 / 2 ) then:

49 ( 3 / 2 ) = [ ( 49 ) ^ 3 ] ^ ( 1 / 2 ) =

[ ( 49 ) ^ ( 1 / 2) ] ^ 3 =

sqrt ( 49 ) ^ 3 =

7 ^ 3 = 343

Correct

2. What is 5^ãx^25y^125 ?

3.

5 x - 2 x + 8 x ^ 2 - 7 =

8 x ^ 2 + 3 x - 7

In a polynomial, the coefficient of the term with the highest degree is called the leading coefficient.

So the leading coefficient = 8

4.

Correct

5.

x = the length of the side parallel to the building

w = the width of the cage

x + 2 w = 100

Subtract 2 w to both sides

x + 2 w - 2 w = 100 - 2 w

x = 100 - 2 w

Area = length * width

A = x * w =

( 100 - 2 w ) * w =

100 w - 2 w ^ 2 =

- 2 w ^ 2 + 100 w

NOT ( - 2 x ^ 2 + 100 w )

A = - 2 w ^ 2 + 100 w

= - 2 * 15 ^ 2 + 100 * 15 =

- 2 * 225 + 1500 =

-450 + 1500 =

1050 ft ^ 2

6.

( 5 x ^ 2 - 2 x + 9 ) + ( 2 x ^ 2 - 4 ) =

5 x ^ 2 - 2 x + 9 + 2 x ^ 2 - 4 =

5 x ^ 2 + 2 x ^ 2 - 2 x + 9 - 4 =

7 x ^ 2 - 2 x + 5

7.

( 10 a ^ 2 - 6 a ) - ( 7 a ^ 2 - 8 a ) =

10 a ^ 2 - 6 a - 7 a ^ 2 - ( - 8 a ) =

10 a ^ 2 - 6 a - 7 a ^ 2 + 8 a =

10 a ^ 2 - 7 a ^ 2 - 6 a + 8 a =

3 a ^ 2 + 2 a

8.

Correct

9.

( a - b ) ^ 2 = a ^ 2 - 2 * a * b + b ^ 2

( 3 x - 4 ) ^ 2 =

( 3 x ) ^ 2 - 2 * 3 x * 4 + 4 ^ 2 =

9 x ^ 2 - 6 x * 4 + 16 =

9 x ^ 2 - 24 x + 16

10.

( 2 x + 4 ) * ( 2 x - 4 ) =

2 x * 2 x + 2x * 4 - 4 * 2 x - 4 * 4 =

4 x ^ 2 + 8 x - 8 x - 16 =

4 x ^ 2 - 16

OR

( a + b ) * ( a - b ) = a ^ 2 - b ^ 2

( 2 x + 4 ) * ( 2 x - 4 ) =

( 2 x ) ^ 2 - 4 ^ 2 =

4 x ^ 2 - 16